Postmortem glycolysis and pork quality. (September 2019) - Stajkovic, S; Vasilev, D; Teodorovic, V; Karabasil, N
Abstract: After an animal is harvested for meat, the skeletal muscle initiates a myriad of biochemical pathways in an attempt to maintain energy homeostasis. Anaerobic glycolysis is responsible for the generation of ATP to help meet energy demand and for the decrease in pH by generating H + . Both the rate and the extent of the post-mortem pH decline are paramount in the context of the development of pork quality attributes, such as color, water holding capacity, and texture. Pale, soft and exudative meat and dark, firm, and dry meat are two of the major quality defects facing the pork meat industry. Because glycolysis has the potential to affect meat quality attributes either positively or negatively, evaluating its regulation post-mortem is fundamental to understanding meat quality. Therefore, the aim of this study was to evaluate factors that affect mechanism of glycolysis. Special consideration will be given to meat quality attributes and development of pork quality defects.